TRANSFORMING PHARMACY EDUCATION IN UNANI SYSTEM OF MEDICINE: A CRITICAL EVALUATION OF ANCIENT, PRESENT, AND FUTURE - Amreen; Saleem, Mohd Nauman; Asif Iqbal Siddiqui (Universal Journal of Pharmaceutical Research, 2025)
This review article illuminates; a brief historical outline of the origin, evolution and current scenario of the Unani system of Medicine (USM) and Ilmul Saidla (Pharmacy), major issues in Pharmacy (Unani) education, training, practice, including lacunas in; course, curriculum, research, and innovation. The promising and constructive revolutionary idea of the educational system that should be implemented by the establishment of the Bachelor, Master, Doctor of Pharmacy, and Doctor of Philosophy degrees in Pharmacy (Unani) is also given. The objective of this futuristic vision is to produce skilled pharmaceutical professionals in USM to meet the requirements of Unani pharmaceutical industries, supervision of dispensaries of hospitals, public healthcare services and to upgrade the text and knowledge of Pharmacy (Unani). This paper offers a unique opportunity to spark meaningful discussions, encourage critical reflection, and guide strategic planning, making it an essential resource for the ongoing enhancement of the new Pharmacy education system in USM, to achieve impactful and positive outcomes. Peer Review History: Received 10 October 2024; Reviewed 11 November; Accepted 20 December; Available online 15 January 2025 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewers: Dr. Wilman Ismael Carrillo Terán, Technical University of Ambato Avda, Ecuador, wilmanct@gmail.com Dr. Wadhah Hassan Ali Edrees, Hajja University, Yemen, edress2020@gmail.com